Rancang Bangun Permainan Interaktif dengan Scratch - Seng Hansun (Ultimatics : Jurnal Teknik Informatika, 2014)
Scratch is a programming language and an online community where people can program and share interactive media, such as stories, games, and animation. In this paper, the author tries to use Scratch in designing and building an interactive game, called Swimming Fish. The project has been done completely and shared to all people through Scratch website. Index terms—game, interactive, project, Scratch, swimming fish